Penerapan Teori Comfort Kolcaba dan Self Care Orem pada Pasca Bedah Sesar Primipara - Aida Kusnaningsih (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Delivery by section Caesarea is surgical to save mother and baby who risk condition and cannot give vaginal delivery. Section cesarean can cause-effect physical, psychological problems, and role nursing to reduce the effect and help the patient. This study aimed to depict the implementation of the nursing with focuses application the theory or comfort Kolcaba and self-care Orem on the case of primipara post-cesarean section. The method used is a case study with the application of the Orem Self Care Theory and Comfort Kolcaba in five cases of women with a post-primiparous cesarean section at Dr. RSUPN. Cipto Mangunkusoma Jakarta The application of theory help post-cesarean patient to comfort/reduced pain and increase ability self-care and newborn.